Sliding Mode Control Strategy for Three-Phase Three-Level T-Type Shunt Active Power Filters - Komurcugil, Hasan; Bayhan, Sertac; Biricik, Samet (IEEE, 2019)
In this paper, a sliding mode control (SMC) strategy is proposed for three-phase three-level T-type shunt active power filters (SAPF). The proposed control strategy has the ability to balance the capacitor voltages with respect to the neutral-point. The proposed SMC strategy is formulated in the natural frame which eliminates abc/dq transformation and two PI controllers compared to the design in the dq frame. In natural frame, only one PI controller is needed to generate the amplitude of grid current reference. The output of the PI controller is multiplied by the unity sinusoidal waveforms, obtained from the grid voltages, so as to obtain the grid current references. The filter current references are obtained by subtracting the measured load currents from grid current references. The performance of the proposed control method is investigated by simulation study during steady-state and transients caused by load change. It is shown that the grid currents are almost sinusoidal with small THD, grid currents and dc-link voltage track their references and capacitor voltages are balanced with respect to the neutral-point.
45th Annual Conference of the IEEE Industrial Electronics Society (IECON) -- OCT 14-17, 2019 -- Lisbon, PORTUGAL
Keywords: Three-level T-type shunt active power filter; proportional-integral control (PI); sliding mode control